FAMILY - A BASIC PILLAR IN THE CARE OF THE ELDERLY AT HOME (PANGEEA, 2025)
As the population ages rapidly and chronic disease rates become more prevalent, families are experiencing a decline in their ability to provide care for the elderly. Society should increase the need for a long-term care policy to provide home care and social support for the elderly who are highly dependent. This paper aims to highlight how the needs of the elderly are met through family home care.
Keywords: home care; family; elderly person; dependency